Environment and gynaecologic cancers - Chandra, Rudrika; Kumari, Sarita (Oncology Reviews, 2024)
In the current era, environmental factors are well established as major causative agents for all cancers especially lung and breast cancer. We sought to review the current available literature on the topic pertaining to gynaecologic cancers. Although a few factors are well established in literature, others need more research to conclude.